Elevational changes in the bacterial community composition and potential functions in a Tibetan grassland - Li, Yaoming; Fang, Zhen; Yang, Fan; Ji, Baoming; Li, Xiangzhen; Wang, Shiping (Frontiers in Microbiology, 2022)
In the Tibetan grasslands, the distribution patterns of the microbial community structure and function along elevation gradients have attracted considerable attention due to the wide distribution of mountain slopes, but the controlling factors of these patterns are still unclear. Here we investigated the taxonomy and potential functions of soil bacteria along an elevation gradient in a Tibetan mountainous grassland in 2 years, aiming to explore the elevation patterns of the bacterial structure and function and the underlying drivers. High-throughput sequencing and environment attribute measurements were conducted to survey the bacterial and environment characters. Furthermore, PICRUSt2 for prediction of bacterial functions, iCAMP for unraveling the drivers controlling community assembly, and HMSC for variance partitioning of bacterial community composition were used. Elevation did not significantly affect the bacterial diversity but changed their composition, driven by both deterministic and stochastic processes. In addition, elevation did not significantly affect the relative importance of deterministic and stochastic processes. Soil carbon, nitrogen, and temperature were important deterministic factors in driving bacterial community structure. The genus Solirubrobacter in Actinobacteriota was identified as most elevation discriminatory. Based on these observations, the bacterial community in the Tibetan mountainous grasslands was more controlled by edaphic factors than temperature, indicating their relative stability under climate change scenarios.